Mosque Management Application Information System at the Baitussyarif Muhammadiyah Mosque in Jambi - Yaakub, Saleh; Marsyaf, Agesha; Ediansa, Oka; Reza, Iqbal Fadhilah; Priyanti, Rida (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The Information System is a technology that can be utilized at the Al-Mujtahidin Mosque to assist the governance management process which is currently being managed manually. As a result, reporting is not transparent and can only be accessed by certain people. With this management information system, it is hoped that it can improve the quality of services at the mosque.. Purpose. The final aim of this research is to improve the quality of Al-Mujtahidin mosque services and provide a more holistic understanding to the congregation or community around the mosque. By gaining a more complete and integrated understanding of religion, science and technology, it is hoped that the congregation will be able to better integrate this knowledge into their daily lives. This will help the Jamaat use technology in the form of better applications, solve complex problems, and face modern challenges with a richer and deeper understanding. Method. In this empowerment, a statistical-based feature extraction method will be applied, namely searching for features characteristic of service conditions based on the level of the activity itself and will be adjusted to the level of service that will be provided to stakeholders. This method is largely determined by the conditions of activity at the Al-Mujtahidin Mosque.. Results. Application and development of information technology for Android-based Al-Mujtahidin mosque services and integration of technology on the internet network, making it easier for mosque congregations to obtain information services at the Al-Mujtahidin mosque. And currently it is still not running optimally and effectively, so there needs to be special guidance efforts for managers, so that mosque services based on the integration of science and technology can run more effectively. Conclusion. Science and technology cannot be separated in people's lives, including from an Islamic perspective. Mosque management information services are urgently needed. Therefore there is a need to utilize information technology in terms of services at mosques which can provide information services regarding mosque activities including, infaq services, sodakoh and information on other routine mosque activities. The application implemented is expected to be able to answer the needs of the current congregation, which is quite large in number. In general, the management will obtain the expected results or goals, because Currently, the Al-Mujtahidin Mosque must be ready for advances in the field. Technology and science are increasingly becoming a part of people's lives and are also able to compete in increasing numbers when compared with other mosques.